Physical variables - lake profile additional logger system from Feresjön, floating platform, 2025-03-28–2025-11-04 - Asa Research Station (Swedish University of Agricultural Sciences, 2026)
High frequency additional logger system measurements of CO2 and/or O2 along a depth profile in the lakes of SITES Water.
Asa Research Station (2026). Physical variables - lake profile additional logger system from Feresjön, floating platform, 2025-03-28–2025-11-04 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Gt9HJLN2ys6jA-v_MxnFE3l1
Keywords: Asa Research Station; Carbon dioxide; Lake; Oxygen; Time instant; Time instant; Dissolved oxygen; Dissolved oxygen; Oxygen saturation; Oxygen saturation; Water temperature; Water temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap